2019
DOI: 10.15407/alg29.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol compounds of macroscopic and microscopic algae

Abstract: Статья посвящена функциональной роли путей биосинтеза и разнообразию полифенольных соединений-продуктов вторичного метаболизма макро-и микроводорослей. Фенольные соединения включены в интегральную систему

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Galland-Irmouli et al [ 196 ] and Samarakoon and Jeon [ 197 ] reported various skin-benefiting activities of protein and amino acids: anti-inflammatory, antioxidant, antitumor, antiaging, skin protective, and moisturizing effects in cosmetic products and the natural moisturizing factor in human skin. Houston [ 198 ] found Ulva australis to be a good source of essential amino acids, such as histidine and taurine. whereas Galland-Irmouli et al [ 199 ], Pereira [ 200 ], and Martínez–Hernández et al [ 201 ] have shown that red alga Palmaria palmata and Himanthalia elongata are a high source of serine, alanine, and glutamic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Galland-Irmouli et al [ 196 ] and Samarakoon and Jeon [ 197 ] reported various skin-benefiting activities of protein and amino acids: anti-inflammatory, antioxidant, antitumor, antiaging, skin protective, and moisturizing effects in cosmetic products and the natural moisturizing factor in human skin. Houston [ 198 ] found Ulva australis to be a good source of essential amino acids, such as histidine and taurine. whereas Galland-Irmouli et al [ 199 ], Pereira [ 200 ], and Martínez–Hernández et al [ 201 ] have shown that red alga Palmaria palmata and Himanthalia elongata are a high source of serine, alanine, and glutamic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are well known secondary metabolites in the plant kingdom not only because of their possible health benefits arising from such as their antioxidant activity, antimicrobial capacity and anticancer property (Belščak-Cvitanović et al, 2018;Bouarab-Chibane et al, 2019;Álvarez-Martínez et al, 2020), but also because of their allelopathic inhibition on nuisance phytoplankton in the aquatic ecosystem (Gao et al, 2017;Tan et al, 2019). Many polyphenols, such as pyrogallic acid (PA), gallic acid (GA), ellagic acid (EA), and (+)-catechin (CA), have been identified in aquatic plants (Nakai et al, 2000;Olate-Gallegos et al, 2019;Zolotareva et al, 2019), and confirmed evidently to have allelopathic inhibition against various cyanobacteria (Huang et al, 2016;Techer et al, 2016;Yu et al, 2019). Polyphenols from natural biomaterials have received more attention as alternatives for emergency control of cyanobacteria bloom because of their algae-inhibiting effects, which is specific to cyanobacteria, biodegradable and less toxic effect to other aquatic organisms (Mohamed, 2017;Tan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…gallic acid and 131.15 mg-eq. quercitin [ 63 , 64 ]. It is known that the content of phenols in microalgae depends on the composition of the medium and growing conditions.…”
Section: Discussionmentioning
confidence: 99%